Test Of Antibacterial Activity and GC-MS analysis of ethyl acetate and N-hexane fractions of Kenitu leaves (Chrysophyllum cainito L.) - Megawati, Sefi; Meta Safitri; Rangkuti, Saru Noliqo; Luthfiyyatul Makiyyah; Arum Mawarni, Nur Indah (Jurnal FARMASIMED (JFM), 2025)
Background: As a result of the large number of infectious diseases, every year 3.5 million people die. The more microorganisms that are resistant to antibiotics, the search for and research into new antibacterials must be carried out from medicinal plant extracts such as the kenitu leaf plant, whose antibacterial activity is still rarely researched. Objectives: to analyze the factors that influence the management of solid media waste of hazardous and toxic materials at RSUD.Kumpulan Pane, Tebing Tinggi City. Research method: This research is a type of laboratory experiment using the semi-polar solvent ethyl acetate and the non-polar solvent n hexane from kenitu (Chrysophyllum cainito L.) leaves to test their antibacterial activity using the disk diffusion method. In this study there were six treatment groups: positive control (+) ciprofloxacin, negative control (-) DMSO 10%, as well as four concentration variations, namely K1: 25 mg/ml, K2: 50 mg/ml, K3: 100 mg/ml, and K4: 500 mg/ml. Results: The results of the ANOVA test of the antibacterial activity test of the Bacillus subtilis fraction against the ethyl acetate fraction obtained a p value <0.001. From the results of the homogeneity test, a significant value of p = 0.023 was obtained. These values ??are in accordance with the criteria (p <0.05), meaning that the concentration treatment has a significant impact on the diameter of the inhibition zone. Based on the results of the two tests, the data obtained in this study were analyzed using the non-parametric Kruskal-Wallis statistical test showing that there was a difference in the average Asymp value in each treatment. Sig. = 0.005 (p <0.05). The results of the Mann-Whitney test of the ethyl acetate fraction on Bacillus subtilis bacteria stated that it had a significant difference in providing an inhibition zone. Conclusion: the analysis stated that there were 27 compounds that were identified in the ethyl acetate fraction and 19 compounds that were identified in the n-hexane fraction of kenitu leaves. The results of testing regarding antibacterial activity stated that the kenitu leaf fraction from ethyl acetate solvent was only able to inhibit the growth of Bacillus subtilis and Staphylococcus aureus bacteria at a concentration of 500 mg/ml, for the kenitu leaf fraction from n-hexane solvent stated that all concentrations were not possible. able to inhibit the growth of Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Bacillus subtilis.